Mídia e eleições presidenciais de 1994 a 2010 : o funcionamento do imaginário na Folha de S. Paulo acerca da corrupção no PT - Zampar, Douglas (2014)
The presidential elections, on its discursive and media operation, are the object of our study. We look upon the group of enunciates produced throughout the electoral period, and the way they produce meaning. To this end, in this dissertation, we took the interface between media and politics and elected the newspaper Folha de S.Paulo to build our corpus. We problematize the imagery of corruption in the Workers Party (PT) function on Folha de S.Paulo and its historicall construction over several elections. Our hypothesis is that there are shifts in how corruption is made into discourse in the last two elections when compared with others. Given that, we propose as a general goal of our research to verify the maintenance and the shifts of the imaginary on Folha de S.Paulo about corruption in PT in presidential elections. To this end, our specific objectives are: a) to analyze statements that constitute networks of meaning that traverse one or more elections, checking shifts and deletions that work on the production of meaning effects; b) to observe the historical constitution of the senses on corruption and PT along different presidential elections coverages by Folha de S.Paulo, discussing the ways in which discursive memory constitutes Imaginary Formations. From theoretical basis on Discourse Analysis, especially the reflections produced around the thought of Michel Pecheux, we operate a constant movement between the analytical and theoretical device constructed throughout the research and the corpus elected to our analysis. We build our research around five presidential elections (1994, 1998, 2002, 2006 and 2010). The questions that move us are oriented around the operation of Imagery Formations, i.e. the senses of what is corruption in PT which crosses the production of meaning effects during campaigns. To do so, we work with the concept of discursive memory, which we understand as a process that produce effects of meaning from the reference of a sentence to a network, so that the meaning is crossed by other statements which entail the production conditions in which they have emerged. Thus, we understand the statement in its historical thickness. Our research shows an imaginary about corruption as a feature of national policy, transcending political parties in the five elections studied. We also perceive a shift of meanings that constitute corruption, which is taken as a violation of laws in the 1994 and 1998 elections, as an immoral practice en 2002 and as immoral and unethical practice in the 2006 and 2010 elections. The imagery of corruption in PT is constituted in 1994 and 1998 on the issue of the use of government, and in 2002 by inserting the issue of morality. The 2006 and 2010 elections demonstrated a shift in how corruption in the PT is approached, because this imaginary starts to work around the corruption scandals.